Quantifiable Cross-cultural Research on Medical Mistrust is Necessary for Effective and Equitable Vaccination in Low- and Middle-income Countries - Sean P. Prall (Journal of Epidemiology and Global Health)
Abstract Perceptions of healthcare personnel and institutions substantially impact healthcare behaviors. In the US, minority experiences with racist events like the Tuskegee study, alongside everyday experiences of marginalization and discrimination, drive medical mistrust in populations that are already burdened with health inequalities. However, the concept of medical mistrust is rarely applied outside of industrialized contexts. Histories of colonialism, underfunded healthcare institutions, and the enormous cultural and ethnolinguistic diversity present in low- and middle-income countries (LMICs) make medical mistrust a likely contributor to health behavior in these contexts. In the era of COVID-19 and emergent malaria vaccines, there is an urgent need to mitigate factors leading to medical mistrust, which impedes interest in novel vaccines. Doing so requires substantial investment in research that examines the causes of medical mistrust across diverse communities, develops methodological tools that can effectively measure medical mistrust across diverse cultural and ethno-linguistic contexts, and applies this data to policy and public health messaging. This commentary highlights the role of medical mistrust in vaccination and argues for its utility in addressing vaccine decision-making in LMICs.